Before Crips: Fussin', Cussin', and Discussin' among South Los Angeles Juvenile Gangs - Quicker, John C. (Studies in Transgression Ser., 2022)
Intro -- Contents -- Acknowledgments -- Map of South Los Angeles in the 1950s -- Introduction -- Insiders Become Outsiders: Methodology -- 1. When the South Came West -- 2. Assemblies of Juveniles -- 3. The Discovery of Gangs in Los Angeles -- 4. Street Group Development: A Storied Evolution -- 5. Slaus Angeles, Villa Fornia 90001: Gang Capital of the World -- 6. The Big Three: Social Class, Gender, and Race -- 7. Comin'-from-the-Shoulders: Ethics, Weapons, Fights, and Violence -- 8. Malicious Mopery on a Public Highway: Crime and Punishment -- 9. Unable to Embrace the Ideology: The Rise of the Crips -- Appendix: South Los Angeles Sets and Car Clubs before 1965 -- Notes -- Bibliography -- Index -- Photos.